Disillusionment on the day of Yahweh with special reference to the land (Amos 5) - Helberg, J. L. (Old Testament essays, 1988)
Amos preaches that the day of Yahweh will hring disiUusionmenL to Israel because God will punish them instead 01 saving.them, even drive them into exile. This meana the end of his promises about the covenant or election. The main reuon is laraeI'. immoraUty, especially their social injustice, in spite of their Uvely cultic activity. This paper calls the attention to the underlying I'l1II80II, D8ID8Iy that Yahweh was not to them the one and all who could only he idantilled in lenDs of Himself and he served for the sake of Himself. In their upectetlon of the day 01 Yahweh, they had made Him Yahweh of the day (oft........vationl and Yahweh of the land (Lheir landl. This theocentric approach of Amoe alao providee the ground for the abrupt message of salvatloa in 9:11-15. Salvation is effected through disillusionment and downfall aDd _made poealble by the Ufegiving grace of God an aspect which should receive more attention than it bas up to now.